Autorzy:Jerzy Janowicz
Wydawnictwo:Nowa Era
Rok wydania:2016
Oblicz 4.71 gwiazdek na podstawie 7 opinii

`a)\ 6^-3*(1/2)^-3+12^-2:24^-2=(6*1/2)^-3+(12:24)^-2=` 

`\ \ \ =3^-3+(12/24)^-2=1/3^3+(1/2)^-2=1/27+2^2=1/27+4=4 1/27` 

 

 

`b) \ 0,01^-4:(-0,1)^-4-20^-3*0,05^-3=(0,01:(-0,1))^-4-(20*0,05)^-3=`  

` \ \ \ =(1:(-10))^-4-1^-3=(-1/10)^-4-1=(-10)^4-1=10\ 000-1=9999` 

 

 

`c)\ 8^-5*(5/4)^-5-35^-5:3,5^-5=(strike8^2*5/strike4^1)^-5-(35:3,5)^-5=` 

`\ \ \ =10^-5-(350:35)^-5=10^-5-10^-5=0` 

 

 

`d)\ 12^-2:6^-2+(-2)^12:(-2)^6=(12:6)^-2+(-2)^(12-6)=` 

`\ \ \ =2^-2+(-2)^6=1/2^2+64=1/4+64=64 1/4 ` 

 

 

`e)\ 0,8^-3*(1 1/4)^-3-(7/8)^5:(7/8)^6=(0,8*1 1/4)^-3-(7/8)^(5-6)=` 

`\ \ \ =(8/10*5/4)^-3-(7/8)^-1=(4/5*5/4)^-3-8/7=1^-3-8/7=1-1 1/7=-1/7`